2018
DOI: 10.3791/56846
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Interaction Kinetics of an Ion Channel Protein with Small Molecules by the Bio-layer Interferometry Assay

Abstract: The bio-layer interferometry (BLI) assay is a valuable tool for measuring protein-protein and protein-small molecule interactions. Here, we first describe the application of this novel label-free technique to study the interaction of human EAG1 (hEAG1) channel proteins with the small molecule PIP2. hEAG1 channel has been recognized as potential therapeutic target because of its aberrant overexpression in cancers and a few gain-of-function mutations involved in some types of neurological diseases. We purified h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The rSCY3, rSCY4, and rSCY5 significantly increased the induced AR ratio, as well rSCY2, indicating that the SCYs could promote the sperm AR. In addition, the BLI assay is emerging as a novel label-free methodology for detecting protein–small molecule interactions by immobilizing a tiny amount of protein sample on the surfaces of biosensor and measuring the optical changing signals [ 64 ]. Additionally, the analysis of recombinant human erythropoietin (rh-Epo)/liposome interactions [ 65 ] showed that small molecule inhibitors (SMI) bound to Tissue transglutaminase (TG2) potently inhibited cancer cell adhesion [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rSCY3, rSCY4, and rSCY5 significantly increased the induced AR ratio, as well rSCY2, indicating that the SCYs could promote the sperm AR. In addition, the BLI assay is emerging as a novel label-free methodology for detecting protein–small molecule interactions by immobilizing a tiny amount of protein sample on the surfaces of biosensor and measuring the optical changing signals [ 64 ]. Additionally, the analysis of recombinant human erythropoietin (rh-Epo)/liposome interactions [ 65 ] showed that small molecule inhibitors (SMI) bound to Tissue transglutaminase (TG2) potently inhibited cancer cell adhesion [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gst empty vector was obtained using the same experimental steps as earlier. These experiments were according to the procedures as previously reported 33,34 …”
Section: Methodsmentioning
confidence: 99%
“…The interaction between cnA protein and DK was detected by using the ForteBio Octet Red system (ForteBio, USA) as the procedures previously described in the literature 34–36 . The GST‐tagged cnA protein and the empty GST protein were immobilized onto Super Streptavidin (SSA) Biosensors (Genemore PNG‐MM‐IGT), and the captured biosensors were individually immersed in the wells containing different concentrations of DK (100, 50, 25, 12.5, 6.25, 3.125 μmol L −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of the binding of Sal A to SrtA were determined by a biolayer interferometry (BLI) assay using the Octet RED96 system (ForteBio, Inc., Menlo Park, CA) as described previously [24]. Ni-NTA sensors were used to bind the His-tag SrtA protein.…”
Section: Biolayer Interferometry Assaymentioning
confidence: 99%